The role of mitochondria in pharmacological ascorbate-induced toxicity - Juan Du; Amanda N. Pope; Brianne R. O’Leary; Brett A. Wagner; Prabhat C. Goswami; Garry R. Buettner; Joseph J. Cullen (Scientific Reports, 2022)
Abstract At pharmacological levels, ascorbate (P-AscH-) acts as a pro-oxidant by generating H2O2, depleting ATP in sensitive cells leading to cell death. The aim of this study was to determine the role of ATP production by oxidative phosphorylation or glycolysis in mechanisms of resistance to P-AscH–induced cell death. Pancreatic cancer cells were used to generate ρ0 cells by mitochondrial overexpression of the Y147A mutant uracil-N-glycosylase or Herpes Simplex Virus protein. The ρ0 phenotype was confirmed by probing for mitochondrial DNA, mitochondrial DNA-encoded cytochrome c oxidase subunit 2, and monitoring the rate of oxygen consumption. In ρ0 cells, glycolysis accounted for 100% of ATP production as there was no mitochondrial oxygen consumption. Even though the activities of H2O2-removing antioxidant enzymes were similar in both the parental and ρ0 clones, P-AscH- -induced clonogenic cell death in ρ0 cells showed more resistance than the parental cell line. In addition, P-AscH- induced more DNA damage and more consumption of NAD+ and greater decreases in the production of ATP in the parental cell line compared to the ρ0 cells. Thus, cancer cells that largely use oxidative phosphorylation to generate ATP may be more sensitive to P-AscH- compared with cells that are glycolysis-dependent.